Boundary conditions and new frontiers for Cognitive UV Radiation Theory - León Eyzaguirre, Federico R. (2018)
Lynn’s (2010) genetic interpretation of the increasing IQ observed from the South to the North of Italy and the debate that followed prompted León and Antonelli-Ponti (this issue) to undertake a study of Italian data in the perspective of UV radiation (UVR) theory (Study 1). The results suggested that UVR degrades intelligence by inhibiting socioeconomic development, which may account for the cognitive North-South divide in that country. The findings contradicted tenets of the cognitive capitalism perspective according to which it is intelligence that increases wealth. In a second study, León and Antonelli-Ponti (this issue, Study 2) found similar relationships among white children of the United States. Unlike in the Italian case, these cannot be attributed to latitudinal genetic variation confounded with UVR’s contemporary effects. A third study in Brazil differentiated the socioeconomic and cognitive impacts of UVR from those of race (León & Antonelli-Ponti, this issue, Study 3).